Caracterização acústica de grandes centros comerciais - António P. O. Carvalho (2015)
This study characterizes the interior acoustics in four large shopping malls in Porto, Portugal by in situ measurements of objective acoustic parameters (reverberation time and background noise levels) comparing these with proposed ideal values and evaluating the influence that the surrounding features have on the results. Results show RT values between 1.7 and 3.2 s and LAeq (with occupancy) between 67 and 70 dB.